PERFORMANCE ANALYSIS OF BOILER FEED WATER PUMP SULZER AT PLTU AT PT INDONESIA CHEMICAL ALUMINA - Julianto, Eko; Fuazen, Fuazen; Gunarto, Gunarto; Sarwono, Eko (Universitas Muhammadiyah Jakarta, 2021)
In this research, boiler feed water pump at PLTU PT.ICA has a flow rate capacity of 85 m3 / h which is installed sporadically with a motor to drive the pump. This pump has an important role and the main pump for filling feed water from dearator into the steam drum (boler) which is always used for 2 years with varying flow rates. Data needed for evaluation include pressure and temperature of the suction, pressure and temperature of the discharge, flow rate and electric current. The data were taken starting in January to Maret 2019. Data processing was performed using a centrifugal pump calculations includes head, water horse power (whp), brake horse power (bhp) and efficiency presented in tables and graphs using Microsoft Excel. Boiler feed water pump sulzer during operations 3 months amounted the highest head amounted 1212,23 m, the highest whp amounted 223,25 kw, the highest bhp amounted 237,21 kw and the highest efficiency amounted 95,67 %, while the lowest head amounted 928,53 m, the lowest whp amounted 72,68 kw, the lowes bhp amounted 197,14 kw and thelowest efficiency amounted 36,85 %. Change of performance bfp occur due to changes flow rate and pressure suction which adjust operational needs.